Wegener’s granulomatosis masquerading as Pansinusitis and Nasal Polyposis: a diagnostic Dilemma (Indian Journal of Case Reports, 2017)
Wegener’s Granulomatosis is characterized by granulomas of the upper and lower respiratory tracts, glomerulonephritis and systemic vasculitis of small and medium sized vessels. A “limited” form of the disease points to the presence of clinical findings restricted to the upper respiratory tract and/or lungs. Limited sino-nasal disease is rare and, coupled with the higher incidence of tuberculosis, bacterial and fungal sinusitis, a timely diagnosis often poses a challenge. We present a case of a female patient in the seventh decade with features of pansinusitis and nasal polyps, initially diagnosed as, granulomatous lesion of infective etiology, which later turned out to be Wegener’s granulomatosis.